Efeitos da capsaicina em células estreladas hepáticas - Bitencourt, Shanna (2012)
Liver fibrosis is the wound healing response to repeated injury of the liver. It is characterized by disruption of the liver architecture associated with increased expression of extracellular matrix components. Hepatic stellate cells (HSCs) play a key role in the process of fibrogenesis. In normal liver, HSCs are quiescent and its main function is to store vitamin A. During liver injury, these cells undergo activation, become myofibroblasts and acquire fibrogenic properties. Capsaicin, the active ingredient of red pepper has been extensively studied in recent years for possessing a wide range of pharmacological properties, including analgesic, anti-inflammatory, antiproliferative and anticarcinogenic in a variety of cell types. Therefore, the aim of this study was to investigate the in vitro effects of capsaicin on deactivation, differentiation and proliferation of HSCs, besides studying the possible mechanisms involved. The results showed that capsaicin is capable of inducing the quiescent phenotype in HSCs via PPARγ activation and blockage of TGF-β signaling. Increased levels of antifibrotic cytokines (IFN-γ and IL-10) and the reduction of pro-inflammatory and pro-fibrotic mediators (COX-2, MCP-1, type I collagen) showed that capsaicin inhibits the activation and migration of these cells. Furthermore, the mechanism used by capsaicin to inhibit cell proliferation is via cell cycle arrest. These findings demonstrate that capsaicin has the potential to be a novel therapeutic agent in the treatment of liver fibrosis due to its antifibrogenic and antiproliferative actions.